Papulonecrotic tuberculid in a patient with pulmonary tuberculosis - Satyendra Kumar Singh; Tulika Rai (Wolters Kluwer Medknow Publications, 2014)
A 55-year-old male presented with recurrent crops of crusted papular lesions and boils over buttocks for 1month along with a short history of productive cough. The diagnosis of papulonecrotictuberculid (PNT) with pulmonary tuberculosis was made based on history, clinical features, laboratory investigations, and response to antitubercular treatment.